2017
DOI: 10.1159/000478733
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Conservative Care Using Sodium Bicarbonate Supplementation Is Associated with a Decrease in Electronegative LDL in Chronic Kidney Disease Patients: A Pilot Study

Abstract: Background: Chronic kidney disease (CKD) patients develop metabolic acidosis when approaching stages 3 and 4, a period in which accelerated atherogenesis may ensue. Studies in vitro show that low pH may increase low-density lipoprotein (LDL) oxidation, suggesting a role for chronic metabolic acidosis in atherosclerosis. The present study attempted to evaluate the effects of conservative care using oral sodium bicarbonate (NaHCO3) supplementation on the electronegative LDL [LDL(-)], a minimally oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…There was measurably noteworthy reduction of triglyceride, absolute cholesterol and LDL-C and increment of HDL-C in treatment bunch after sodium bicarbonate treatment and this isn't concordant with [26]. Our clarification is there was increment of FT3 and FT4 in treatment bunch after sodium bicarbonate treatment.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…There was measurably noteworthy reduction of triglyceride, absolute cholesterol and LDL-C and increment of HDL-C in treatment bunch after sodium bicarbonate treatment and this isn't concordant with [26]. Our clarification is there was increment of FT3 and FT4 in treatment bunch after sodium bicarbonate treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Besides, adjustment of MA in patients with CKD causes T3 levels to ascend towards ordinary (25). Additionally, [26], reasoned that in a gathering of CKD stage 2-4 patients, the utilization of oral NaHCO3 supplementation for the remedy of MA was related with a lessening in serum levels of LDL (-), a negligibly oxidized LDL. These discoveries establish proof for a useful impact of salt treatment to forestall LDL oxidation, which has significant ramifications for atherogenesis in CKD patients [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty remaining studies were scrutinized in detail, and 37 articles were excluded because of: 1) using intravenous sodium bicarbonate, 2) co-supplementation of sodium bicarbonate with vitamin C, 3) using vegetables and fruits as an intervention in control group, 4) not reporting relevant data, or 5) enrolling subjects with acute kidney injury. Finally, 13 studies met all inclusion and exclusion criteria were included in this systematic review and meta-analysis (3,4,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) Characteristics of the included studies are presented in Table 1. Participants were from Hong Kong, Israel, Thailand, Chinese, Brazil, Italy, South Korea, England, Thailand, and the USA.…”
Section: Resultsmentioning
confidence: 99%
“…The results of sensitivity analysis revealed that excluding the Rizetto et al study (14) attenuated bene cial effect of sodium bicarbonate on serum creatinine. This study showed a signi cant reduction in serum creatinine after sodium bicarbonate administration, however, the reported con dence interval for changes in serum creatinine was very short in this study compared with other included studies.…”
Section: Discussionmentioning
confidence: 97%